Perlindungan Hukum Bagi Debitor Apabila Terjadi Kepailitan Dan Penundaan Kewajiban Pembayaran Utang Pada Suatu Perusahaan (Studi Putusuan Mahkamah Agung Nomor 442 K/Pdt.Sus-Pailit/2012)) - Widiantari, Nilka; Apriani, Rani (Jurnal Ilmiah Wahana Pendidikan, 2024)
The0objective0of0this0study0is0to0examine0how0the0Supreme0Court0Decision0Number 442 K/Pdt.Sus-Pailit/2012 addresses issues related to bankruptcy., as well as to elucidate the legal safeguards provided to debtors in the context of bankruptcy and PKPU in a commercial setting. by the use of normative juridical research techniques, such as the utilization of legal materials found in statutes or libraries. The author employs relevant books, papers, documents, articles, and other scientific works in addition to legal sources for gathering legal materials. This study employs a statutory and regulatory method to solve the problem, making it normative legal research in the sense that it evaluates relevant rules. Essentially, once the debtor has finished the bankruptcy procedure, Creditors who0believe0that0their rights0have0not0been fully satisfied can pursue the collection of the money owing to them in accordance0with the0relevant0rules and0regulations.